Gender-affirming Mastectomy with Concurrent Oncologic Mastectomy. Issue 2 (9th February 2022) - Boyd, Carter J.; Blasdel, Gaines; Rifkin, William J.; Guth, Amber A.; Axelrod, Deborah M.; Bluebond-Langner, Rachel
Abstract : Background: Transmasculine individuals may not have undergone gender-affirming mastectomy and retain natal breast tissue. Our center offers simultaneous oncologic mastectomy with gender-affirming reconstruction to patients who are diagnosed with breast cancer. This study is the first reported series of concurrent gender-affirming and oncologic mastectomies. Methods: A retrospective chart review of all patients undergoing gender-affirming mastectomy at a single institution from February 2017 to October 2021 was performed. Patients were included who had breast cancer diagnoses or pathologic lesions preoperatively. Demographic factors, comorbidities, surgical details, and oncologic history were collected. Both plastic surgery and breast surgery were present for the gender-affirming oncologic mastectomies. Results: Five patients were identified who presented for gender-affirming mastectomy in the context of breast pathologies. Average patient age was 50.2 ± 14.8 years, and no patients used testosterone at any time. Two (40%) patients had a prior breast surgery that included a breast reduction in one patient and breast conserving lumpectomies in another. Sentinel lymph node biopsies were performed in all patients. Only one patient had a positive sentinel lymph node and was subsequently referred for postoperative radiation and chemotherapy. No oncologic recurrence has been detected with 20.6 and 10.0 months of mean and median follow-up. Conclusions: When performed in a multidisciplinary and collaborative setting with breast surgeons and plastic surgeons, oncologic mastectomy can be performed safely while concurrently offering patients an aesthetic gender-affirming reconstructive outcome.